Analisis Peran Telemarketing dalam Penawaran Produk di Perusahaan Trustmedis - Monica Shinta Uli; Dewi Khrisna Sawitri (Universitas Muhammadiyah Surabaya, 2024)
This research aims to analyze the role of telemarketing in the product offering of Trustmedis, a Software-as-a-Service (SaaS) based technology company that provides cloud-based digital solutions to support health facilities in Indonesia from independent doctor's practices, laboratories, pharmacies, health centers, clinics to hospitals. Trustmedis' product is Electronic Medical Record (RME) software which requires a special approach considering its non-physical and complex characteristics. Telemarketing, both inbound and outbound, is used to introduce products, build customer trust, and collect data on potential customers. This research uses qualitative methods with observations during the internship period and interviews with internal and external parties from Trustmedis. The results of this research show that telemarketing plays an important role in increasing awareness and facilitating application demo sessions as the first step in customer conversion. However, there are challenges in conveying information which must be more structured, using concrete examples, and a more persuasive approach. This research contributes to developing marketing strategies in the field of health facility technology and offers recommendations for increasing the effectiveness of telemarketing.